Riches among the ruins : adventures in the dark corners of the global economy - Smith, Robert P. , 1940-; Zheutlin, Peter (American Management Association, 2009)
Details the financial-oriented adventures of Robert P. Smith, who has made and lost millions by making risky investments in troubled economies around the world, and describes his trips to Baghdad, Vietnam, Guatemala, and other places.